Two new earthworms of the Pheretima sangirensis species group (Clitellata: Megascolecidae) from Mountain Province, Philippines - Hong, Yong; James, Samuel W. (Zootaxa, 2021)
Two new species of the genus Pheretima are described from Mt. Amuyao and Mt. Lamagan, Mountain Province, Philippines, namely Pheretima riparianensis sp. nov. and Pheretima bontocensis sp. nov. Both new species belong to the P. sangirensis species group characterized by having only one pair of spermathecal pores in 7/8. Pheretima riparianensis sp. nov. has distance between spermathecal pores 1–2 mm; copulatory bursae openings 0.11 circumference ventrally apart. Pheretima bontocensis sp. nov. has distance between spermathecal pores 1.4 mm; copulatory bursae openings 0.10 circumference ventrally apart.